TOXIC PEOPLE DAN DAMPAKNYA DI ‎DALAM AL-QUR’AN (ANALISIS TERHADAP ‎PENAFSIRAN BUYA HAMKA DALAM TAFSIR ‎AL AZHAR)‎ - Butar Butar, Nurul Azzahra (UIN Sumatera Utara Medan, 2021)
This research is motivated by the issue of increasingly diverse human behaviors, diminishing morals, and a lack of empathy toward others. People often hurl harmful words at one another, impacting relationships in families, friendships, communities, and even social media. Such individuals are often labeled as